Design, Synthesis, and Molecular Docking Studies of Sulfonyl-Substituted Chromene Derivatives as Anticancer Agents - Rai, Aman; Soni, Arti; Bhatia, Rohit (Synlett, 2025)
This study explores the role of estrogen in breast cancer development through ERα and ERβ receptors and highlights the significance of aromatase in estrogen biosynthesis. Chromene-based compounds, known for their anticancer properties, were synthesized with sulfonyl substitutions to enhance their efficacy. The MTT assay on MCF-7, MDA-MB-231, and HCT-116 cancer cell lines showed that (Z)-N-(3-cyano-2H-chromen-2-ylidene)benzenesulfonamide (AN1) and (Z)-N-(6-bromo-3-cyano-2H-chromen-2-ylidene)methanesulfonamide (AN13) had strong cytotoxic activity. Aromatase inhibitory assay shows that compound AN1 and AN13 show good inhibitory activity with IC50 values 0.20 and 0.24 μM. Docking studies revealed that these compounds fit well at the active site of the aromatase enzyme, with AN1, AN2, AN3, AN7, AN8, and AN13 showing docking scores of –9.1, –9.0, –8.8, –8.0, –8.6, and –7.8, respectively, compared to Exemestane with –9.3. ADME predictions indicated good drug-like properties, suggesting that these chromene derivatives could be effective anticancer agents.
Keywords: chromene; anticancer; aromatase; breast cancer; cell lines; exemestane